Evaluación del desempeño eléctrico de estructuras de diferentes materiales empleadas en redes de distribución (2018)
In this paper, the electrical behavior of structures is assessed considering conductive and non-conductive materials for a pole-crossarm arrangement. To achieve this, AC and impulse tests are performed for a typical distribution structure used in Empresas Públicas de Medellín (EPM) distribution system and composed by pole and crossarm for different combination of materials. From the result obtained by the impulse test, it is possible to stablish the contrast with the critical flash overvoltage (CFO) reference values published in the IEEE Std. 1410. Finally, the low-frequency behavior is verified by means electrostatic field simulation using the finite element analysis.